Flexibility Fatigue in the It Industry: A Matricentric Exploration of Working Women’s Remote Work Struggles - Deogaonkar, Anant; Tolani, Kanchan; Vichoray, Chandan; Lanjewar, Ashay; Shraddha, Chandra (Journal of Posthumanism, 2025)
This study explores the phenomenon of flexibility fatigue among Indian working women in the IT industry through a matricentric lens. The sudden shift to remote work, accelerated by the COVID-19 pandemic, has blurred work-life boundaries and intensified the caregiving responsibilities of women, especially mothers. While flexibility is designed to enhance work-life balance, this research highlights how it often results in perpetual availability, mental exhaustion, and emotional strain. Semi-structured interviews with 30 Indian working mothers were conducted and analysed thematically, revealing key challenges such as work-life boundary erosion, gendered household pressures, lack of organizational empathy, psychological strain, and the pressing need for supportive structures. The findings emphasize the intersectionality of gender, culture, and professional expectations, demonstrating the systemic neglect of women’s unique challenges in remote work models. This research contributes to theories of boundary management, role strain, and feminist organizational studies, while also offering actionable recommendations for organizations and policymakers to design gender-sensitive policies that promote mental health, caregiving support, and career equity. Future research is recommended across sectors and genders to further understand flexibility fatigue’s broader implications.